The relationship between inflammation and the development of cerebral ischaemia and hypoxia in traumatic brain injury: a narrative review - Nimmo, Alan J.; Younsi, Alexander (International journal of molecular sciences, 2025)
Traumatic brain injuries (TBI) represent a leading cause of morbidity and mortality globally. Whilst clinical care has significantly improved in recen...